Making Necrotizing Vasculitis Simple. Issue 4 (July 2013) - McCourt, Collette; Dutz, Jan P.
Background: Cutaneous necrotizing vasculitides (CNV) represent a heterogeneous group of inflammatory diseases affecting the skin blood vessels, characterized histologically by transmural inflammation of the blood vessel wall with fibrinoid necrosis and clinically characterized by palpable purpura, leading to ulceration. These syndromes represent a spectrum of disease from limited cutaneous small vessel vasculitis to rapidly progressive systemic vasculitis. Moreover, a number of diseases can mimic vasculitis in the skin, thereby presenting diagnostic difficulties for physicians. Objective: We present an update of CNV and vasculopathies based on recent literature and clinical experience. We provide a dermatologic approach to the patient presenting with purpura and ischemic skin necrosis focusing on the subtle features that may help physicians discern between primary and secondary causes and the differences between vasculitis and vasculopathy.